Electrically conducting graphene/SiC(111) composite coatings by laser chemical vapor deposition. (November 2018) - Xu, Qingfang; Deng, Zhao; Sun, Qingyun; Tu, Rong; Zhang, Song; Yang, Meijun; Li, Qizhong; Zhang, Lianmeng; Goto, Takashi; Ohmori, Hitoshi
Abstract: Graphene/SiC (G/SiC) composite coatings with <111>-orientation were in-situ deposited using hexamethyldisilane (HMDS) as precursor by laser chemical vapor deposition (LCVD). The concentration and distribution of graphene sheets in SiC matrixes were controlled by changing total pressure ( P tot ) in the reaction chamber. The investigation of growth mechanism showed that the photolytic of laser played an important role during the depositions. Observation by high-resolution transmission electron microscopy (HRTEM) revealed that graphene nucleated on SiC(111) lattice planes. As the increase of P tot, the concentration of graphene decreased and the grain size of SiC grains and graphene sheets increased. The distribution of graphene in SiC matrix significantly affected the electrical conductivity (σ) of the composite coating. The highest σ is over 2 orders of magnitude larger than that of the graphene/semiconductor composites fabricated by other strategies. The high σ makes the G/SiC(111) composite coating very promising for the applications in mechanical, energy, and sensor-related areas. Graphical abstract: Image